The Fiscal Costs of Earthquakes in Japan - Ilan Noy; Toshihiro Okubo; Eric Strobl; Thomas Tveit (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We investigate the fiscal impacts of earthquakes in Japan. In contrast with earlier papers from elsewhere which examine national level aggregate spending, we are able to provide a detailed examination of separate budget categories within the local governments' fiscal accounts. We do this using detailed line-budget expenditure data, and by comparing regions and towns affected and unaffected by the damage from earthquakes. Besides the obvious - that government spending increases in the short-term (one year) after a disaster event - the results we present suggest that the share of public spending on disaster relief, at the prefecture level, increases significantly, but with no corresponding change in the other budget lines. In contrast, at the lower administrative units we observe a decrease in the share of spending going to finance other priorities. For the bigger cities, we observe a decrease in the share of spending targeting education, while for the smaller towns, we find that spending on construction and servicing public debt goes down. This evidence suggests that while at the prefecture level fiscal policy-making is robust enough to prevent presumably unwanted declines in public services, the same cannot be said for the city/town level.
Keywords: H84; Q54; 330; fiscal costs; earthquakes; Japan